Supporting Undergraduate Research Symposia in the Sciences: Integrated Library Programming and Services. Issue 4 (2nd October 2017) - Leligdon, Lora; Harding, Katie
ABSTRACT: Libraries are always looking for innovative ways to support the undergraduate research process. One way to provide this support is to offer an integrated suite of programs and services for undergraduate researchers in the sciences as they create and present research posters at a science symposium. The Dartmouth College Library developed a series of programs, including a symposium preparation session, library research award, and winner exhibit to increase support, expand outreach activities, and develop strong collaborations with students and other research support departments on campus. These programs help the library demonstrate value by supporting students as they disseminate their research.